2014
DOI: 10.1590/1809-4503201400060002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neighborhood empowerment and dental caries experience: a multilevel study in adolescents and adults

Abstract: ABSTRACT:Objective: To investigate the relationship of contextual social capital (neighborhood empowerment) and individual social capital (social support and social network) with dental caries experience in adolescents and adults. Methods: A population-based multilevel study was conducted involving 573 subjects, 15-19 and 35-44 years of age, from 30 census tracts in three cities of Paraíba, Brazil. A two-stage cluster sampling was used considering census tracts and households as sampling units. Caries experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Authors examining the relationship between social context and dental caries occurrence found that the community context affects caries prevalence [Aida et al, 2008] and showed a beneficial associa- tion between community empowerment [Patussi et al, 2006a, b;Santiago et al, 2014] and social cohesion [Aida et al, 2008], both indicators of SC, and dental caries. Guedes et al [2014], using a multilevel analysis, observed that living in areas with a low social network and unfavourable social conditions had a great impact on a child's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Authors examining the relationship between social context and dental caries occurrence found that the community context affects caries prevalence [Aida et al, 2008] and showed a beneficial associa- tion between community empowerment [Patussi et al, 2006a, b;Santiago et al, 2014] and social cohesion [Aida et al, 2008], both indicators of SC, and dental caries. Guedes et al [2014], using a multilevel analysis, observed that living in areas with a low social network and unfavourable social conditions had a great impact on a child's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of perceived social support and low numbers of social networks were independently associated with dental caries in adolescents [Bernabé et al, 2011;Fontanini et al, 2015]. In addition, low neighbourhood empowerment was an important variable related to caries experience [Santiago et al, 2014]. On the other hand, two studies involving similar age groups were unable to support the association between social relationships and oral health.…”
Section: Discussionmentioning
confidence: 89%
“…The presence of community centres has shown significant associations with decay scores (Aida et al, 2008), with improvements in oral health also linked with institutions such as churches (Tellez et al, 2006). Neighbourhood level empowerment has also shown negative associations with decay experience (Santiago et al, 2014), although not all studies have found links between oral health and social capital (Mathur et al, 2016). The location of dental surgeries may also influence oral health due to some areas being underserved (Lang et al, 2008).…”
Section: The Determinants Of Tooth Decay: Key Theoretical and Researc...mentioning
confidence: 99%